2013
DOI: 10.1103/physrevb.88.155201
|View full text |Cite
|
Sign up to set email alerts
|

Systematic study of defect-related quenching of NV luminescence in diamond with time-correlated single-photon counting spectroscopy

Abstract: We report on the systematic characterization of photoluminescence (PL) lifetimes in NV − and NV 0 centers in 2-MeV H + -implanted type Ib diamond samples by means of a time-correlated single-photon counting (TCSPC) microscopy technique. A dipole-dipole resonant energy transfer model was applied to interpret the experimental results, allowing a quantitative correlation of the concentration of both native (single substitutional nitrogen atoms) and ion-induced (isolated vacancies) PL-quenching defects with the me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 62 publications
(139 reference statements)
1
53
0
Order By: Relevance
“…With the higher nitrogen concentration of 212 pm NV 0 does not occur and all centres acquire an electron. The behavior is almost independent of the NV − concentration, an aspect well illustrated by figure 4 of [42]. Their figure shows spectra for two nitrogen concentrations each with widely varying NV − concentrations.…”
Section: Low Intensitymentioning
confidence: 61%
See 1 more Smart Citation
“…With the higher nitrogen concentration of 212 pm NV 0 does not occur and all centres acquire an electron. The behavior is almost independent of the NV − concentration, an aspect well illustrated by figure 4 of [42]. Their figure shows spectra for two nitrogen concentrations each with widely varying NV − concentrations.…”
Section: Low Intensitymentioning
confidence: 61%
“…For example it has been shown earlier in figure 20(b) that the rate for the 212 ppm N 0 sample is faster than for the 115 ppm N 0 sample. Large variation in rates have been reported in the literature and for 1b diamonds the shorter lifetimes correlate with the higher nitrogen concentrations [15,[42][43][44][45]. The best illustration is in a recent paper by Bogdanov et al [46] where they have shown that for micro-diamonds prepared by HPHT there is a systematic shortening of the lifetime with nitrogen concentration Figure 22.…”
Section: Emission Changes and Lifetimesmentioning
confidence: 93%
“…Previous works report that lifetime changes of color centers evidence interaction with various defects [12][13][14] as well as the photonic environment. 15 (9) ns], potentially due to a decrease in the effective refractive index close to the nanoscale apex.…”
mentioning
confidence: 99%
“…As it is known, one of the unique properties of diamond is a very high thermal conductivity among all solids, including all metals, natural minerals and rocks (Monticone et al, 2013;Dement'ev, Voiloshnikov, & Kononko, 2015;Makarskii, 2012;Fedorov, Chepurov, & Dereppe, 2002;Chanturiia et al, 2012). An analysis of thermal physical properties shows that, in comparison with diamond grains, kimberlite, rocks and related minerals from deposits are characterized by a much lower level of thermal conductivity -by ~ 2-3 orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%